A comparative analysis of nondescent vaginal hysterectomy, laparoscopy-assisted vaginal hysterectomy, and total laparoscopic hysterectomy for benign uterine diseases at a rural tertiary care center - Vaibhav Kanti; Vandana Verma; Mamta Singh; Soniya Vishwakarma; Nupur Mittal; N P Singh (Gynecology and Minimally Invasive Therapy, 2022)
Objectives: The aim of this study was to compare operative data and postoperative complications among nondescent vaginal hysterectomy (NDVH), laparoscopy-assisted vaginal hysterectomy (LAVH), and total laparoscopic hysterectomy (TLH) at a rural tertiary care center. Materials and Methods: This is a prospective analytical study, of 145 hysterectomies for benign conditions with or without salpingo-oophorectomy in women from 30 to 60 years, over 3 years from January 2016 to December 2019, with 60 cases of NDVH, 46 cases of LAVH, and 39 cases of TLH. The three groups were compared intraoperatively in terms of blood loss, operating time, and intraoperative complications and postoperative complications and postoperative duration of hospital stay. Results: There was no significant difference between the three groups in terms of age, parity, body mass index, and indications for hysterectomies. The mean operative time was significantly shorter (P = 0.000) in the NDVH group (54.67 ± 15.67 min) as compared to the LAVH (102.45 ± 10.53 min) and TLH (126.79 ± 8.7 min) groups. Intraoperative blood loss was greater (P = 0.000) in the TLH group (111.025 mL ± 20.8) as compared to the NDVH (59.50 mL ± 16.7) and LAVH (91.85 mL ± 10.66) groups. The intraoperative complications and postoperative complications were higher in the TLH group as compared to the LAVH and NDVH groups. The duration of hospital stay was almost similar in all the groups. Conclusion: NDVH may be the preferred approach for experienced surgeons, as it is less time-consuming, has a small amount of blood loss, and is a scarless surgery, whereas LAVH and TLH may be the preferred approaches in the cases of presence of adnexal masses and adhesions or whenever salpingo-oophorectomy is indicated.